KARAKALPAKSTAN AS PART OF THE RSFSR (1930-1936) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article highlights one of the interesting events in the life of Karakalpakstan as part of the Russian Federation. Based on the previous historiography, introducing new archival documents into scientific circulation, the authors will try to assess the political, socio-economic and cultural state of the republic during this period.